ANALISIS HUBUNGAN MASSA OTOT LENGAN DAN KEKUATAN GENGGAMAN TANGAN PADA PERFORMA SHOOTING PEMAIN BOLA BASKET - Abdul Aziz Hakim; Fatkur Rohman Kafrawi; Mokhamad Nur Bawono; Ruri Rani Dara Putri (JURNAL ILMU KEOLAHRAGAAN, 2026)
This study aims to analyze the relationship between arm muscle mass and handgrip strength on basketball players' shooting performance. A sample of 21 basketball players from the Surabaya State University student league used long-range shooting or three-pointers as a research indicator. The study used a quantitative cross-sectional design. Arm muscle mass was measured using BIA, handgrip strength using a handheld dynamometer, and shooting performance through a 10-shot three-pointer test. Shapiro–Wilk analysis showed a normal distribution of the data, so the Pearson correlation test was then used. The results showed a positive and significant relationship between arm muscle mass and three-pointer shooting percentage (strong relationship) and between handgrip strength and three-pointer shooting percentage (moderate relationship). These findings indicate that upper extremity strength plays an important role in the stability and control of long-range shooting or shooting performance, but still depends on the player's technique and neuromuscular control.